1875 Ind. Acts 59 - (:unkn) unknown (My University, 1875)
Ch. 40 § 1-2: Prohibited the sale, barter, or transfer of any pistol, dirk, Bowie-knife, slung-shot, knuckles, or other deadly weapon to any adult under the age of twenty-one. Violators guilty of a misdemeanor and fined not less than five but no more than fifty dollars.
Keywords: TRANSFER - MINORS